Neurobiological mechanisms of control in alcohol use disorder – Moving towards mechanism-based non-invasive brain stimulation treatments. (February 2022) - Ghin, Filippo; Beste, Christian; Stock, Ann-Kathrin
Highlights: AUD is characterised by an imbalance between cognitive control and automaticity. Pathological changes in fronto-striatal activity seem to underlie this imbalance. We propose that neuromodulation techniques could help target these AUD mechanisms. NIBS-based therapy could effectively reduce consumption and decrease relapse rate. NIBS might also help restore the balance between controlled and automatic behaviour. Abstract: Alcohol use disorder (AUD) is characterized by excessive habitual drinking and loss of control over alcohol intake despite negative consequences. Both of these aspects foster uncontrolled drinking and high relapse rates in AUD patients. Yet, common interventions mostly focus on the phenomenological level, and prioritize the reduction of craving and withdrawal symptoms. Our review provides a mechanistic understanding of AUD and suggests alternative therapeutic approaches targeting the mechanisms underlying dysfunctional alcohol-related behaviours. Specifically, we explain how repeated drinking fosters the development of rigid drinking habits and is associated with diminished cognitive control. These behavioural and cognitive effects are then functionally related to the neurobiochemical effects of alcohol abuse. We further explain how alterations in fronto-striatal network activity may constitute the neurobiological correlates of these alcohol-related dysfunctions. Finally, we discuss limitations in current pharmacological AUD therapies and suggest non-invasive brain stimulation (like TMS and tDCS interventions) as a potential addition/alternative for modulating the activation of both cortical and subcortical areas to help re-establish the functional balance between controlled and automatic behaviour.